A pulse transformer for a 10 MW klystron power supply - Bak, P.A.; Kazarezov, I.V.; Kobets, V.V.; Korepanov, A.A.; Krainov, G.S.; Radchenko, V.I.; Severilo, V.S.; Tuvik, A.A. (Вопросы атомной науки и техники, 2001)
The design and test results of the Pulse Transformer (PT) for the klystron with a voltage of 120 kV, klystron current of 130 A and a pulse duration of 1.4 ms is presented. The PT design was realized with taking into account the following requirements: no edge effect on the secondary winding; no overvoltage along the secondary winding at the klystron breakdown; random high voltage breakdowns may occur only between metal parts, not on the windings; the sharp voltage edge applied to the primary winding should not cause a turn-to-turn overvoltage.